On the essence stage of criminal case. (Journal of actual problems of jurisprudence, 2016)
The article is devoted to actual problems of stage of criminal case. The article deals with questions about the essence of the first stage of criminal procedure and its place in the criminal justice system, reasons and grounds for a criminal investigation, analyzed the adoption procedure, registration and preliminary examination reports of crimes. Special attention is paid to the problems of application of special knowledge of the stage of a criminal case, as well as on the interaction of investigators and bodies of inquiry at this stage of the criminal process.
Keywords: criminal proceedings instituted; criminal trial; questioning; investigation; preliminary investigation